Efficacy of Nano-urea in Flowering and Fruiting of Litchi Cultivars Grown under the sub-Himalayan Terai Region of West Bengal - Bhowmick, Nilesh; Aresh, Jinnamu; Parameshwar, Polu; Chamling, Novin; Santhoshkumar, G. M.; Senjam, Bidyarani Devi (International Journal of Economic Plants, 2025)
A scientific investigation was carried out in 2021 during January to June at Uttar Banga Krishi Viswavidyalaya, Pundibari, Cooch Behar, West Bengal, India, to evaluate the flowering and fruiting behavior of litchi (Litchi chinensis Sonn.), a subtropical fruit species indigenous to South China and Southeast Asia. The crop holds substantial economic significance in India, with West Bengal recognized as one of the major litchi-producing states. The application of nanostructured urea fertilizer, referred to as “Nano-urea,” has been demonstrated to enhance crop yields while mitigating the environmental pollution associated with conventional fertilization practices. So, this study was conducted to evaluate the effects of treated and non-treated nano-urea fertilizers on various growth and quality parameters in litchi cultivars. The experiment comprised 14 treatments, with a primary focus on fruiting parameters and several fruit quality attributes. The results indicated significant variations among treatments, with T12 showing the highest total number of flowers (637.10), the highest percentage of fruit set (2.25), and notable fruit quality metrics, including a fruit weight of 12.18 g and TSS of 15.70°Brix. Conversely, T3 recorded lower metrics, particularly for fruit weight (14.50 g) and TSS (13.55°Brix). Overall, treatments involving nano-urea resulted in improved fruit attributes compared with the non-treated controls. These data suggest that the application of nano-urea positively influences flower and fruit development, thereby enhancing the overall quality of litchi cultivars. These findings highlight the potential of urea as a viable option for optimizing litchi production and quality.